'Newmarket, that Infamous Seminary of Iniquity and Ill Manners': Horses and Courts in the Early Years of George III's Reign. (2nd September 2019) - Cox, Oliver
Abstract : This article explores the role played by different types of equine culture — haute école and horse racing — in the turbulent politics of the early years of George III's reign. It suggests that opponents to Lord Bute politicised the racecourse, and in particular Newmarket, in order to challenge the men and measures of the court of St James's. Whilst Newmarket can be understood as a significant alternative to London as a site of aristocratic politicking, those eager to court favour with Lord Bute also tried to share his love of Spanish-bred horses.